REGIONAL TAX SERVICE QUALITY STRATEGY RIGHTS TO LAND AND BUILDING IN THE CITY OF BEKASI - Asep Kusdiman Jauhari; Wahyudin Wahyudin; Kamal Alamsyah (Lembaga Penelitian Universitas Pasundan, 2021)
The main problem in this research is that the service quality strategy of the Regional Tax on Acquisition of Land and Building Rights (BPHTB) in Bekasi City has not been effective. The research method used by researchers is descriptive analysis with this type of research is qualitative. Qualitative methods are chosen with the consideration that this method is expected to obtain real data and is able to study research problems in depth so that the expected results can be obtained. Based on the results of the analysis, that there are strategic factors that can improve the quality of local tax services for land and building rights acquisition fees in Bekasi City, namely structural development strategy factors, development or simplification strategies, infrastructure development strategies, cultural or cultural development strategies and development strategies. entrepreneurship However, in its implementation there are strategic factors that have not been running effectively, namely entrepreneurial development strategy factors, so that there are still problems faced related to improving the quality of local tax services for Acquisition of Land and Building Rights in Bekasi City. This of course also has not been able to provide the best way to provide quality public services, especially with regard to local tax services for Acquisition of Land and Building Rights in Bekasi City.